Triceps-reflecting anconeus pedicle approach with double precontoured locking plate fixation is efficient in the treatment of orthopaedic trauma association type C distal humerus fracture. Issue 10 (October 2016) - Chou, Ying-Chao; Hsu, Yung-Heng; Yu, Yi-Hsun; Wu, Chi-Chuan
Abstract: Background: The purpose of this study was to determine if the triceps-reflecting anconeus pedicle (TRAP) approach combined with the precontoured locking plate can provide acceptable clinical outcomes in the treatment of comminuted distal humerus fracture. Methods: Between August 2008 and June 2014, 48 patients with Orthopaedic Trauma Association type C (21 with C2, 27 with C3) distal humerus fractures underwent open reduction and internal fixation with orthogonal precontoured locking plate fixation using the TRAP approach. Occurrences of bony union, implant failure, posttraumatic arthrosis, and heterotopic ossification were detected with radiography. Clinical assessment included evaluation of range of motion and determination of the pain score, Mayo Elbow Performance Index (MEPI) score, and Disability of the Arm Shoulder and Hand (DASH) score. Results: The fractures healed within 3 months in 25 patients (53%) and within 6 months in 23 patients (47%). The 12-month assessment revealed improved elbow movement, with the mean arc of flexion-extension of 121° (range, 100°–140°), mean arc of supination-pronation of 163° (range, 150°–180°), and mean flexion contracture of 8° (range, 0°–30°). The mean MEPI score was 81 and the mean DASH score was 11.7. Conclusions: By retaining the intact olecranon by the TRAP approach, orthopedic surgeon can get adequate surgical exposure for fracture fixation and can use olecranon as a three-dimensional template to restore the articular fragments. The promising results in this study obtain because that precise identification of the triceps muscle allowed the determination of a proper length-tension relationship for triceps reattachment. The combination of triceps tendon repair and anconeous muscle repair ensured the strength of the extensor mechanism. Therefore, the TRAP approach in combination with the usage of the precontoured locking plate can be recommended as the optimal surgical approach for the treatment of comminuted distal humerus fracture.